The Dead Sea Scrolls and the Nag Hammadi Codices Selected Papers from the Conference "The Dead Sea Scrolls and the Nag Hammadi Codices" in Berlin, 20-22 July 2018 - Burns, Dylan M.; Goff, Matthew J. (Brill, 2022)
The discoveries of Coptic books containing "Gnostic" scriptures in Upper Egypt in 1945 and of the Dead Sea Scrolls near Khirbet Qumran in 1946 are commonly reckoned as the most important archaeological finds of the twentieth century for the study of early Christianity and ancient Judaism. Yet, impeded by academic insularity and delays in publication, scholars never conducted a full-scale, comparative investigation of these two sensational corpora-until now. Featuring articles by an all-star, international lineup of scholars, this book offers the first sustained, interdisciplinary study of the Dead Sea Scrolls and the Nag Hammadi Codices.